How good are epigeic earthworms at dispersing? An investigation to compare epigeic to endogeic and anecic groups. (August 2017) - Chatelain, M.; Mathieu, J.
Abstract: Dispersal capacities can strongly determine an individual's ability to respond to changing environmental conditions, which would consequently influence the structure of natural communities. Nonetheless, we know little about the dispersal behaviour of soil organisms, despite some of these organisms, such as earthworms, have key roles in ecosystem functioning (e.g. organic matter decomposition). We expect that species exposed to frequent environmental changes would benefit from the capacity to escape from adverse environmental conditions and to disperse to settle in a more suitable habitat. In earthworms, we expect the epigeic group, which lives at or close to the soil surface, to have evolved higher dispersal capacities than the two other functional groups – anecic and endogeic, which live deeper in the soil. In this study, we investigated dispersal and diffusion behaviour of three species of epigeic earthworms (i.e. Eisenia fetida, Eisenia andrei and Lumbricus rubellus ) and compared these behaviours with those of anecic and endogeic earthworms, whose behaviour has been previously measured through similar experiments. In accordance with our hypothesis, our study shows that dispersal behaviour of epigeic earthworms depends on habitat quality and population density, but that those responses vary among species and that it differs only to a limited extent from behaviour of anecic and endogeic earthworms. Highlights: Epigeic earthworm exhibited a higher dispersal rate from low than from high habitat quality. Endogeic earthworms had poorer dispersal capacities than epigeic and anecics. Response to population density was not consistent among epigeic species. Functional group poorly explain dispersal behaviour variability between species. Habitat quality seems a strong driver of earthworm spatial distribution.